Tobacco Control Regulations for National Public Health Law Protection Through Regulatory Instruments - Tuhuteru, Justian Stanley; Pakpahan, Novritsar Hasitongan; Mujito, Mujito (Bulletin of Science, Technology and Society, 2025)
This study analyses the normative character of tobacco control regulations in Indonesia within the framework of public health protection, focusing on three key instruments tobacco advertising regulations that restrict promotion, the establishment of smoke-free areas (SFAs) in various public spaces, and the obligation to include pictorial and text health warnings on product packaging. Through a normative legal research approach, this study examines the national regulatory framework, such as the Health Law, Government Regulation No. 109/2012, Minister of Health Regulation No. 56/2017, BPOM Regulation No. 18/2025, and various related regional regulations. The results of the analysis show that these three instruments complement each other in establishing a legal system that prioritises the right to health and protects the public from the effects of tobacco consumption. These regulations represent restrictions on the commercial interests of the industry for the sake of public health. The study concludes that although the existing regulatory framework has strengthened the legal foundation for health protection, its effectiveness depends heavily on consistent enforcement, continuous monitoring, and the ability to adapt to new tobacco products and innovative marketing methods.